2019
DOI: 10.37134/ejoss.vol5no1.4
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi tekanan akademik dan kesejahteraan diri di dalam kalangan pelajar universiti di Serdang, Selangor

Abstract: AbstrakKajian ini telah dijalankan untuk menentukan perkaitan antara persepsi tekanan akademik dengan kesejahteraan diri dalam kalangan pelajar universiti di Serdang, Selangor. Seramai 400 orang pelajar telah dipilih sebagai responden kajian dan data dikumpul menggunakan borang soal selidik yang diisi sendiri oleh responden. Skala Personal Wellbeing Index -Adult (PWI-A) oleh Cummins (2013) digunakan untuk mengukur tahap kesejahteraan diri pelajar universiti. Pesepsi tekanan akademik pula telah diukur dengan me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
2
0
3
Order By: Relevance
“…In terms of psychological well-being, the results of the study also found that there was no significant difference between the levels of psychological well-being according to gender. The findings of this study are consistent with the study by Johari and Ahmad [29] who stated that there is no significant difference in personal well-being between male and female students. A study by Zainal [10] on the psychological well-being of students during COVID-19 also stated that there was no difference between male and female students in terms of the level of psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In terms of psychological well-being, the results of the study also found that there was no significant difference between the levels of psychological well-being according to gender. The findings of this study are consistent with the study by Johari and Ahmad [29] who stated that there is no significant difference in personal well-being between male and female students. A study by Zainal [10] on the psychological well-being of students during COVID-19 also stated that there was no difference between male and female students in terms of the level of psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Johari and Ahmad [29] also stated that the academic demands that need to be met by university students cause anxiety in academic achievement and it affects the level of well-being of students. This researcher also found that the perception of workload and exams is a direct predictor of the well-being of university students.…”
Section: Discussionmentioning
confidence: 99%
“…Tekanan akademik yang berlebihan turut memberi risiko yang tinggi terhadap kesejahteraan dan kesihatan fisiologi, fizikal, emosi dan mental pelajar termasuklah memberi kesan terhadap masalah kebimbangan (Mohammad Arif & Sa'odah, 2019). Kajian lepas mendapati bahawa terdapat hubungan negatif antara tekanan akademik dan kebimbangan di mana individu yang mempunyai tahap prestasi akademik yang rendah adalah mereka yang mempunyai tahap kebimbangan yang tinggi (Yong Yang & Pinzen Yang, 2022;Chen & Lan, 2020).…”
Section: Latar Belakang Kajianunclassified
“…Jadual 1 menunjukkan tahap tekanan akademik responden yang di kategorikan kepada tiga tahap iaitu rendah, sederhana dan tinggi. Pengkelasan kategori ini dilakukan melalui rujukan daripada sumber kajian lepas yang menggunakan instrumen yang sama (Mohammad Arif & Sa'odah, 2019;Aiken & West, 1991). Hasil kajian menunjukkan majoriti responden (73.7%, n=154) mengalami tahap tekanan akademik yang sederhana, 19.1% (n=40) tahap tinggi dan 7.2% (n=15) tahap rendah.…”
Section: Tahap Tekanan Akademikunclassified
See 1 more Smart Citation